The Effectiveness of Using Game-Based Quizizz in Teaching Vocabulary (An Experimental Study of The Eleventh-Grade Students of SMAN 2 Pujut) - Sisnawati, Meisy; Melani, Boenista Zulanda; Thohir, Lalu (Journal of English Education Forum (JEEF), 2024)
This research aims to determine the effectiveness of using Game-Based Quizizz on the vocabulary mastery of eleventh-grade students at SMAN 2 Pujut. This research was pre-experimental research with one group pre-test-post-test design. The population in this research was class XI IPA 1 students at SMAN 2 Pujut. The sampling technique used in this research was a purposive sampling technique with one experimental class. The results obtained from the data analysis showed that the mean score of the pre-test was 30.71 and after treatment, the mean score of the post-test increased to 68.06. Data collection was divided into three steps i.e., pre-test, treatment, and post-test. A result with a significance value of 0.00 was found and the significance value obtained was lower than the alpha value i.e., 0.05.  The test results showed that the significance value (α) is lower than the value (0.00 > 0.05), meaning that the use of Game-Based Quizizz is effective. Therefore, the use of Game-Based Quizizz is very effective for teaching vocabulary to students and can effectively improve students’ vocabulary mastery.